Interplay of eco-friendly factors and islamic religiosity towards recycled package products: A cross-cultural study - Zhang, Qingyu; Husnain, Mudassir; Usman, Muhammad; Akhtar, Muhammad Waheed; Ali, Saqib; Khan, Mussadiq Ali; Abbas, Qamar; Ismail, Riffat; Rehman, Tayyab; Akram, Muhammad (Frontiers in Psychology, 2022)
Climate change has increasingly been recognised and associated with consumer behaviour: Practitioners are developing their strategies to reduce environmental degradation while increasing the management of sustainable consumption; it needs to better understand consumer attitudes and eco-friendly factors about the issue. Therefore, the current study focused to understand the effects of pro-environmental factors on individuals’ environmental attitudes (purchase behaviour towards products with recycled packaging) through the lens of theory of planned behavior in a cross-cultural setting. Moreover, present research focuses on the moderating role that religiosity plays in causal pathways between certain determinants (attitude, subjective norms, and perceived behavioural control) and intentions in this context. A multi-wave time-lagged research design was employed in this study, and university students from two developing countries were surveyed (N=324, 266). The findings revealed pronounced similarities between the two examined countries. Overwhelmingly, pro-environmental factors examined (environmental values, environmental knowledge, and environmental concern) were found to be positively related to attitude formation. Further results showed that attitude and subjective norms are significant predictors of the intention to purchase products with recycled packaging. Moreover, with the exception of perceived behavioural control, religiosity moderates the relationships between all the determinants of TPB and intention to purchase recycled packaged products. Present study offers insightful implications to management of these emerging and/or similar cultural markets regarding customer value for green products. Using TPB, present study broadened and deepen extant stream of literature on consumption of recycled packaged products in two highly emerging markets; Pakistan and Malaysia.